The Community Service Empowering Teachers To Apply Seft (Spiritual Emotional Freedom Techniques) For Smoking Students At Vocational School 2 Samarinda City - Syukma Rhamadani Faizal Nur; Muhammad Aminuddin; Iwan Samsugito; Mayusef Sukmana; Dwi Nopriyanto; Muhammad Bagas Prayoga (Fakultas Kedokteran, Universitas Mulawarman, 2023)
Adolescence is a period when individuals have a strong desire and adventure about everything they have never known. Exposure to tobacco at an early age will not only make you a lifelong smoker but will also increase the risk of contracting non-communicable diseases (PTM) such as heart disease, chronic respiratory disease, diabetes, and cancer as an adult. SEFT is a therapy that combines psychological energy with spirituality to improve emotional, mental, and behavioral conditions with three simple techniques, namely set-up, tune-up, and tapping. The purpose of this activity is to equip SMKN 2 Samarinda teachers to understand the SEFT process and then apply it to their students so they can stop smoking behavior. The method used is the post-test by assessing the teacher's skills in performing the SEFT technique. The result of this community service is that teachers are proficient in doing SEFT. So it is hoped that consistency from teachers in carrying out this SEFT therapy to students, so that smoking behavior in students can be reduced or even stop smoking.